Situation Report: Poland, 29 April 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Labor Unrest Continues / by Louisa Vinton Independent and Official Commemorations of the Warsaw Ghetto Uprising / by Louisa Vinton Poland Re-examines Its Jewish Past / by John Reed The Banking System to Be Reorganized / by Roman Stefanowski The Official Press Documents Police Brutality / by Louisa Vinton